Porencephaly and Periventricular Encephalitis in a 4-month-old Puppy: Detection of Canine Parvovirus Type 2 and Potential Role in Brain Lesions. (May 2019) - Marenzoni, M.L.; Calò, P.; Foiani, G.; Tossici, S.; Passantino, G.; Decaro, N.; Mandara, M.T.
Summary: A 4-month-old puppy died after showing intracranial signs a few days after a suspected viral enteritis. Grossly, the right cerebral hemisphere had a large irregular cavity external to the internal capsule. Histopathological examination revealed a cystic lesion in the right hemisphere and non-suppurative inflammation of the diencephalon and periaqueductal nervous tissue. Porencephaly associated with periventricular non-suppurative encephalitis was diagnosed. A nested polymerase chain reaction (PCR) identified the presence of parvovirus DNA in the brain and real-time PCR typed this as canine parvovirus (CPV) type 2a. Immunohistochemistry revealed the presence of CPV antigen in the cytoplasm of scattered cells in the subependymal layers and choroid plexus epithelium. The porencephaly was not associated with inflammatory lesions or CPV antigen and was considered to have preceded the neurological signs. In contrast, the detection of CPV antigen in the subependymal layers and choroid plexus epithelium supported the association of this virus with the periventricular encephalitis. Graphical abstract: A 4-month-old puppy died with intracranial signs a few days after suspected viral enteritis. Immunohistochemistry revealed a marked cytoplasmic canine parvovirus (CPV)-immunoreaction of scattered cells in the subependymal layers in association with non-suppurative inflammation of the diencephalon, mesencephalic aqueduct and fourth ventricle (Figure). The detection of CPV-2a DNA was also positive.Image 1